(untitled) (Global Journal of Human-Social Science, 2012)
This paper focuses on the nexus of collaboration among the horizontal organs of government in Nigeria in the context of effective service delivery and politics of hope for the nation and its citizens While specifically examining the three organs of government and their institutional mechanisms of separation of powers and checks and balances in the process it elucidates the concepts of politics budgets servant leadership and governance It dichotomizes the latter into two good and bad governance with detailed analysis of the imperatives of both and their implications for the pursuit of effective service delivery for the citizenry in any nation like Nigeria